COMMUNITY PARTICIPATION OF TEMUKU AYA SUBAK TOUR DEVELOPMENT IN VILLAGE OF TAJEN, PENEBEL DISTRICT, TABANAN REGENCY - Dewi, Gusti Ayu Putu Indah Trisna; Pantiyasa, I Wayan (Institut Pariwisata dan Bisnis Internasional, 2017)
The purpose of this research was to know the tourism potential of Temuku Aya Subak Tour seen from 3A that were an attraction, access, and facility. In addition, to know the participation of local communities, as well as the impact of Temuku Aya Subak Tour development to the local community. Temuku Aya Subak Tour is located in Tajen Village and developed by local people who see the potential of tourism in this village.Data collection techniques used were in-depth interviews, observation, and documentation. The analysis technique used was descriptive qualitative analysis and also Triangulation data. The results showed Temuku Aya Subak Tour had the potential of natural rice fields and plantations. Temuku Aya Subak Tour also offered tourism activities as well as the preservation of local culture and traditions. In addition, local communities also participated as investors and as employees in the development of Temuku Aya Subak Tour. The tour economic impact could provide employment. From the socio-cultural impact, it could keep the local customs and traditions of the village, and from environmental impact, the local community could be more aware of the cleanliness of the village environment.